2014
DOI: 10.1080/08897077.2014.958207
|View full text |Cite
|
Sign up to set email alerts
|

Marijuana and Alcohol Use and Attempted Smoking Cessation in Adolescent Boys and Girls

Abstract: Background To determine the relationship between the frequency of current marijuana and alcohol use and cigarette-quit attempts in male and female adolescent smokers. Methods Data from a cross-sectional survey of health behaviors in high-school-age adolescents were analyzed. Current cigarette smokers (n=804) who reported use of at least 1 cigarette in the past month were divided into those with and without a history of at least 1 quit attempt (a self-reported episode of trying to “stop smoking”). Logistic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
3
1
Order By: Relevance
“…No data were available on the extent of addiction of smoking, though this has previously been shown to be associated with cessation [ 14 ]. Similarly, other studies have demonstrated an association between frequency of adolescent drug and alcohol use and making a quit attempt [ 15 ]; we found no significant associations between reported substance use and use of cessation support, though our definition of substance use was less detailed compared to other studies as we were not able to identify frequency of cannabis use or binge drinking from the survey dataset.…”
Section: Discussioncontrasting
confidence: 42%
“…No data were available on the extent of addiction of smoking, though this has previously been shown to be associated with cessation [ 14 ]. Similarly, other studies have demonstrated an association between frequency of adolescent drug and alcohol use and making a quit attempt [ 15 ]; we found no significant associations between reported substance use and use of cessation support, though our definition of substance use was less detailed compared to other studies as we were not able to identify frequency of cannabis use or binge drinking from the survey dataset.…”
Section: Discussioncontrasting
confidence: 42%
“…Simultaneously, there is a negative cohort effect, suggesting that the largest increases in frequent cannabis use are observed among older rather than younger cohorts; that is, frequent cannabis use is increasing more rapidly among those born before 1995 than those born after 1995. Observed trends are consistent across sex, parental education and race/ethnicity and across different cut‐points for the definition of ‘frequent’ cannabis use, a term that is inconsistently defined in the literature . While trends are consistent even when stratified by demographic groups, the relationship between demographic groups and frequent cannabis use are themselves shifting across time.…”
Section: Discussionmentioning
confidence: 84%
“…Binge-Drinking-Severity Groups: As previously described (Camenga et al 2014), participants were stratified into one of four drinking groups: non-drinking, non-binge-drinking, low-frequency-binge-drinking, and high-frequency-binge-drinking. Participants with no lifetime alcohol use were classified as non-drinking.…”
Section: Methodsmentioning
confidence: 99%